A Study on Bacterial Disease of Betelvine in West Bengal, India - Bhattacharya, R.; Mondal, B.; Ray, S. K.; Khatua, D. C. (International Journal of Bio-resource and Stress Management, 2012)
Betelvine (Piper betle L.) is an important cash crop in West Bengal. This crop is commonly affected by stem rot and leaf spot disease caused by two different genera of bacteria- Xanthomonas axonopodis pv. betlicola and Pseudomonas betle. Two bacterial pathogens enter into the host through stomata, hydathode and injury. Both the bacteria, at any portion, of the vine stem form prominent dark brown lesions. Surface of such lesion becomes sticky in humid condition. Occasionally small brown cracked lesions are found on the stem. Such lesion is formed due to infection of X. a. pv. betlicola. On the leaf, small to large, circular to irregular and/or angular brown colored spots and marginal leaf blight symptoms are produced by both the bacteria. All types of spots are surrounded by yellow halo or the halo is present in between brown and green tissue. At the under side of the leaf, the brown lesion is encircled by a water soaked zone or water soaked area, which is found in between brown lesion and green tissue in marginal blight. In addition, yellow colony forming bacterium, X. a. pv. betlicola produces very small brown spot surrounded by prominent yellow halo but without water soaked zone. Frequently both the bacteria have been detected from same leaf spot or stem lesion. Association of these bacteria increases disease severity. Initially the bacteria colonize in parenchyma tissue and later move into vascular tissue. After entry into the vascular tissue X. a. pv. betlicola becomes systemic, produces no further lesion but causes sudden wilting of vine. Such situation causes much damage of the plantation in West Bengal. Pre-inoculation treatment with streptomycin and oxy-tetracycline hydrochloride greatly reduces lesion expansion.